The R.M.S. Abroad (Res Medica, 2014)
When Ted Duvall asked me to write a description of the Leiden trip, I went away and scribbled down the events as they occurred, in chronological order, right down to the last cup of coffee, the last Bokma. I did this because I was afraid that the events, put out of focus, even at the time, by the action of various euphoric agents, would in due course shift themselves beyond recall. Dutch Geneva, and another beverage which went down well with us — Trapiste Triple (Trapiste because made by Trappist monks, triple because about three times stronger than normal beer) — these were not solely responsible for the dreamlike quality of our eight days in Holland. In fact, by our last day, we were all helpless with fatigue. It had all started on the night train from Edinburgh to King's Cross — not a sleeper, of course; that would have been contrary to the essential character of the trip. Most of us didn't sleep at all. We played Bridge till four and then stared disconsolately out into the grey murk, jealous of the slumbering Ailsa and her valium. (Although, to be fair, she did offer us all a fix.) It was even worse in London because we had to spend three hours of the early morning hanging around in Liverpool St. Station, shivering and looking more and more haggard. Finally, some of the party chose to live apart for the duration of the voyage from Harwich to the Hook of Holland. It was becoming clear that there were to be only two big disgraces on this trip — sleeping, and vomiting. (The rest of us relaxed on deck or in the bar, charmed, along with our cosmopolitan fellow passengers, by the colourful and extrovert behaviour of some of our fellow countrymen — who seem to turn up wherever you go — entertaining us with their stirring songs and quaint partisan chants.